2018
DOI: 10.21834/ajqol.v4i15.184
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Characters of Good Street for Greater Urban Quality of Life

Abstract: This conceptual paper aims to demystify how the quality of streets could facilitate the street culture and shaping greater urban qualities. Numerous scholars believed that certain streets had contributed an utmost factor in shaping man's civilisation. The development of modern cities has contributed to a great loss of streets significance as spaces for socialising and dwelling in the local peoples' needs. The outcome of this paper is hoping to guide the practitioners, policy makers and urban designers to incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…This study focuses on the spatial dimension of QoL, categorizing parameters into eight key areas: residential, transport, securitysafety, environment, socio-cultural, recreational, educational, and health. Transportation, residential, and environmental dimensions exhibit the highest number of parameters, reflecting their integral roles in urban life (Ab Rahman et al, 2019).In recent decades, evidence, exemplified by Zhang et al (2017), underscores urban green areas' substantial contribution to residents' overall quality of life. Cities prioritize values like security, peace, health, spatial quality, and ecological features, with open-green spaces crucial to achieving these goals.…”
Section: Literature Review 21 Landscape Spaces and Urban Quality Of Lifementioning
confidence: 99%
“…This study focuses on the spatial dimension of QoL, categorizing parameters into eight key areas: residential, transport, securitysafety, environment, socio-cultural, recreational, educational, and health. Transportation, residential, and environmental dimensions exhibit the highest number of parameters, reflecting their integral roles in urban life (Ab Rahman et al, 2019).In recent decades, evidence, exemplified by Zhang et al (2017), underscores urban green areas' substantial contribution to residents' overall quality of life. Cities prioritize values like security, peace, health, spatial quality, and ecological features, with open-green spaces crucial to achieving these goals.…”
Section: Literature Review 21 Landscape Spaces and Urban Quality Of Lifementioning
confidence: 99%
“…Studies by Ja'afar (2014), Sulaiman & Shamsuddin (2010) and Shamsuddin (1997) found that rapid development and urbanization in Malaysia have a significant impact on the functioning of streets as open public spaces. Development towards of a more modern town has contributed to a great loss of streets significance as spaces for socializing and dwelling in the local people's needs (Ab Rahman et al 2019). Shukri et al (2018Shukri et al ( ,2017 and Harun et al (2015) revealed that extensive development growth occurring in most historical towns have significantly eroded the identity, sense of place and physical attributes of the Malay royal town in Malaysia.…”
Section: Background and Issuesmentioning
confidence: 99%